Programmable Supercontinuum Laser Spectrum Generator Based on a Liquid-Crystal on Silicon Spatial Light Modulator - García-Martínez, Pascuala; Moreno, Ignacio; Sánchez-López, María del Mar; Gomis, Jordi; Martínez, Pedro; Cofré, Aarón (Frontiers in Physics, 2021)
Supercontinuum (SC) lasers combine a broadband light spectrum with the unique properties of single-mode lasers. In this work we present an optical system to spectrally filter a SC laser source using liquid-crystal on silicon (LCoS) spatial light modulators (SLM). The proposed optical system disperses the input laser and the spectrally separated components are projected onto the LCoS-SLM, where the state of polarization of each wavelength is separately modulated. Finally, recombining the modulated spectral components results in an output laser source where the spectrum can be controlled dynamically from a computer. The system incorporates two branches to independently control the visible (VIS) and the near infrared (NIR) spectral content, thus providing a SC laser source from 450 nm to 1600 nm with programmable spectrum. This new ability for controlling at will the wide spectra of the SC laser sources can be extremely useful for biological imaging applications.